Eneolithic and Bronze Age of the Forest Zone of Eastern Europe: disharmony of archaeological periodization - Karmanov Victor N.; Lychagina Evgenia L.; Zaretskaya Natalia E. (Поволжская археология)
The results of the study of the discrepancies problem between regional cultural and chronological schemes in the context of the modified "system of three centuries" are presented. The study is based on the materials of the Garino and Chirki cultures, which sites are located in the extreme northeast of Europe, and on the results of radiocarbon dating of the Eneolithic and Bronze Age complexes of the Eastern European Plain forest zone. The disharmony of the archaeological periodization is expressed in the presence of both populations of the culture attributed to the Late Bronze Age and the Eneolithic culture in the studied region. As a result, it was determined that the sites with Chirkovsko-Seiminskiy or Fatianoid pottery types including the complexes of the Atamannur culture, are synchronous with the Garino culture within the Eneolithic or the 2nd half of the 3rd millennium B.C. However, the main arguments in favor of the Eneolithic of the Chirki culture are the use of pure copper artefacts together with intensive flint knapping with a developed bifacial industry. Therefore, it is predicted that existing ideas about the periodization of early metal sites in north-eastern Europe will be corrected. The comparison of radiocarbon dates showed that complexes with porous and asbestos pottery with sparse decoration (Orovnavolok XVI and Pelya types) are generally older than the pottery of the Garino (Choinovty) culture. This complicates the problem of the origin of the latter, since it is likely that its ceramic traditions originated to the west of the extreme north-east of Europe.